IMPLEMENTASI APRIORI PADA DATA KECELAKAAN LALU LINTAS DALAM PENCARIAN RELASI ANTAR VARIABEL PELAKU - Rusmin Saragih (UIN Sumatera Utara, 2017)
Handling traffic accidents can be done by taking steps such as the approach of socialization and supervision of road signs and traffic. To be able to find the appropriate solutions to the prevention of information required traffic accidents that occur. By observing the relevant variables of traffic accident perpetrators, it can be obtained the criteria from the traffic accident perpetrators that are dominant from the relations of LAKA actors such as education, age and other variables. Apriori applied to data of LAKA actors from recent years to be able to obtain information relation between variator of LAKA actor so that can become reference to prevention and prevention of traffic accident. The a priori output of the laka perpetrator data provides the pattern relation information of the LAKA actor’s variable. Keywords: Data Mining, Apriori, Traffic Accident